A Feasible Option before Cycle Cancellation for Poor Responders; STOP-START Protocol - Cem Somer Atabekoğlu; Yavuz Emre Şükür; Batuhan Özmen; Murat Sönmezer; Bülent Berker; Ruşen Aytaç (International Journal of Fertility and Sterility, 2021)
Despite the advances in controlled ovarian stimulation (COS), management of a subgroup of poor ovarian responderpatients may still be challenging. We describe a feasible and simplified protocol, namely the STOP-START protocol,for poor responders defined as Patient-Oriented Strategies Encompassing Individualize D Oocyte Number (POSEIDON)groups 3 and 4, who are unresponsive to COS with maximum dose gonadotrophins. Data of 11 women unresponsiveto COS were reviewed. Mean age of the patients was 36.5 ± 6.0 years. Unresponsiveness was defined as no follicular growth >9 mm and/or estradiol level less than 40 pg/ml after a week of recombinant follicle stimulating hormone (rFSH, 225-300 IU) administration. In that case, COS was stopped and each woman underwent weekly ultrasound assessment to catch a secondary follicular growth. All women showed at least one follicular growth within five to 20 days. Six women (54.5%) had spontaneous follicular growth and the other five required ovarian stimulation. At least one oocyte was retrieved from each one of seven patients (63.6%). The mean number of oocytes retrieved was 1.6 ± 1.4 and five women (45.5%) had at least one grade A embryo. Among all, two women became pregnant successfully and both gave live births (18.2%). In conclusion, STOP-START protocol may potentially be an effective, feasible, and time-saving management option for POSEIDON group 3/4 poor responders who are unresponsive to standard COS treatment with maximum dose gonadotrophins.